Efektivitas Project Based Learning Berbasis Audio Visual dalam Pembelajaran Surah Pendek Pendidikan Agama Islam pada Siswa SD - Femi Astika Candra Chairani; Ichwanudin (Jurnal Pendidikan Nusantara, 2023)
This research aims to determine the effect of the Project Based Learning (PJBL) improving learning outcomes in Islamic Education subjects. Innovation in the Project Based Leadrning (PJBL) model is a present as a solution that can solve the challenges of today’s times and tecnology to improve the learning outcomes to stodent of Muhammadiyah Elementary School. This research uses a qualitative descriptive method, with a type of library research or historical research using interviews and field observation models. To guarantee the correctness of the data or validate the data, use data triangulation trough three stages, namely data collections, data reductions, and data presentation. The result is an incrase in student learning outcomes in Islamic Education Subject with the audio visual and project based learning. Students quickly memorize and understand the content and asbabun nuzul (the reasons for the revelation of a surah or verse) from a short surah